2022
DOI: 10.1002/wfp2.12050
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of wild edible plants to household livelihood in a semiarid Kondoa District, Tanzania

Abstract: Wild edible plants (WEPS) are an important source of nutrients and income particularly to poor households. However, information on how WEPS contribute to rural livelihoods varies due to heterogeneous methodologies and settings. This paper is based on a study that investigated the contribution of WEPs on rural livelihoods in semiarid Kondoa District, Dodoma Region, Tanzania. Mixed methods were used to collect data from 343 households (14.32%), comprising six focus group discussions and six key informant intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…In addition to having higher ( f ) and (UR) indices obtained in Table 4 , the majority of wild fruit species recorded in this ethnobotanical study have low market values. This assertion is consistent with [ 54 ], who earlier observed that income from selling wild fruits is more for subsistence than as a capital asset for the household in the semi-arid Kondoa District of Tanzania. Very few wild fruits were sold in urban areas for cash generation.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to having higher ( f ) and (UR) indices obtained in Table 4 , the majority of wild fruit species recorded in this ethnobotanical study have low market values. This assertion is consistent with [ 54 ], who earlier observed that income from selling wild fruits is more for subsistence than as a capital asset for the household in the semi-arid Kondoa District of Tanzania. Very few wild fruits were sold in urban areas for cash generation.…”
Section: Discussionsupporting
confidence: 92%
“…The Food and Agriculture Organization of the United Nations (FAO) estimates that up to 1.6 billion people-almost 25% of the world's population-rely on these resources every day for their livelihoods (FAO, 2015). For example, in Tanzania, Mwajombe et al (2022) found that IWEPs provided income in about one in ten households in the study accounting for 10% of the total household income.…”
Section: Introductionmentioning
confidence: 89%